Studi Perbandingan Perusahaan Perseorangan (Sole Proprietorship) Dan Koperasi (Cooperative) Pada Negara Laos & Indonesia - Heriawan, Andi Rahmat (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This study focused to conduct a comparative study of the legal form about individual company (Sole Proprietorship) and a Cooperative. This research using Normative legal research to examine legal rules related to corporate law in a country. The legal form of an individual company (sole proprietorship) is contained in the Laos